Determination of the antibacterial activity of crude extracts and compounds isolated from Hortia oreadica (Rutaceae) against oral pathogens - Severino,Vanessa Gisele Pasqualotto (2009)
Extracts from Hortia oreadica afforded four dihydrocinnamic acid derivatives, isolated from the n-hexane extract, as well as limonoid guyanin and the furoquinoline alkaloid dictamnine, both isolated from the dichloromethane extract. The extracts and the isolated compounds were tested against some oral pathogens, so as to investigate their antibacterial activity. The results showed that the n-hexane extract and the compound dictamnine are the most active against the selected microorganisms.